Clinical Symptoms of Carpal Tunnel Syndrome and Its Correlation With Vitamin D Level - Andira Larasari; Rima Anindita; Andini Aswar; Yudhisman Imran (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Carpal tunnel syndrome (CTS) is a common entrapment neuropathy of the peripheral nerves in the upper extremities that is often found in workers. Nerve conduction disorders occur due to compression of the carpal tunnel, resulting in motor and sensory symptoms in the hands and wrists. This causes clinical symptoms and characteristic neurophysiological examinations. Vitamin D is an intrinsic factor that causes CTS which is now widely studied and is expected to play a role in the choice of CTS management. Vitamin D is important for maintaining health and has been found to have neuroprotective function. Several studies have proven the association between vitamin D deficiency and the incidence of CTS. Supplementation can improve clinical symptoms and neurophysiological features of mild to moderate CTS patients.